Pharmacoeconomic analysis of using biological agents for uncontrolled moderate-to-severe atopic asthma in the Russian Federation - S. K. Zyryanov; I. N. Diyakov; S. N. Avdeev (Фармакоэкономика)
Objective – to conduct a pharmacoeconomic analysis of using omalizumab, mepolizumab and reslizumab in the treatment of patients with uncontrolled moderate and severe atopic asthma in the healthcare setting of the Russian Federation.Materials and Methods. A pharmacoeconomic model based on clinical data was created. The cost-effectiveness ratios for omalizumab, mepolizumab and reslizumab were calculated and compared. Budget impact analysis for the partial replacement of omalizumab with mepolizumab and/or reslizumab has been performed.Results. The use of omalizumab costs 13.3% less than that of reslizumab and 1.6% more than that of mepolizumab. The cost-effectiveness ratio for omalizumab is significantly lower vs the competitors. To prevent asthma exacerbations by omalizumab requires 463 805 rubles, which is 24.80% less than for reslizumab and by 382,640 or 20.89% less than for mepolizumab. The results are robust and resistant to 10% fluctuations in prices for the compared products. According to the budget impact analysis, by introducing reslizumab instead of omalizumab for a 3-year therapy in 210 patients with asthma and blood eosinophilia ≥400 cells/µl, will increase the burden on the budget by 13.25% or by 83.2 million rubles. In a group of 594 patients with eosinophilia ≥150 cells/µl, using mepolizumab instead of omalizumab will increase the budget burden by 1.58% or by 24.0 million rubles. In the total group of 759 patients receiving genetically-engineered products, switching to mepolizumab and reslizumab will increase the budget spending by 3.3% or 67.2 million rubles for 3 years.Conclusion. The analysis shows that using omalizumab in patients with severe asthma that is uncontrolled by medium and high doses of inhaled corticosteroids, has the lowest burden on the budget of the healthcare system and is more effective compared to mepolizumab and reslizumab.